Strategi Komunikasi Media Sosial Instagram @Hondatrenalamsutra dalam Meningkatkan Penjualan Produk - Jody Halfan; Mochamad Mirza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the social media communication strategy implemented by Honda Tren Alam Sutra through the Instagram account @HondaTrenAlamSutra to enhance brand awareness and product sales. A descriptive qualitative method was used to understand the approach and effective implementation of communication strategies. The results of the study indicate that accurate audience identification, the use of engaging visual content, and the utilization of Instagram features such as Stories, Feeds and Reels successfully increased brand awareness and follower engagement. Promotional content such as discounts, sales bonuses, and product education proved effective in capturing follower attention. The marketing team utilized Instagram Insights to measure content performance based on demographic data and engagement metrics, while also adapting strategies based on follower feedback and industry trends. Through data-driven communication strategies and continuous evaluation, @HondaTrenAlamSutra successfully retained followers and attracted new audiences, thereby increasing conversions into sales. This research provides valuable insights for other companies seeking to optimize their social media communication strategies on Instagram.